Grõbner bases and minimum distance of affine varieties codes - Carvalho,C. (2012)
We present a method to estimate the minimum distance of affine varieties codes. Our technique uses properties of the footprint of an ideal obtained by enlarging the defining ideal of the variety, and may be applied also to codes which do not come from the so-called weight domains.